Electrically tunable photo-aligned hybrid double-frequency liquid crystal polarisation grating. Issue 12 (26th September 2018) - Li, Song-zhen; Liu, Yong-gang; Liu, Chun-Jie; Zhao, Zhi-Wei; Wang, Cheng-Miao; Peng, Zeng-Hui; Wang, Qi-dong; Xuan, Li
ABSTRACT: A polarisation grating (PG) based on the hybrid photo-aligned double-frequency liquid crystal has been demonstrated and fabricated in this paper. The single-order diffraction efficiency is above 95% for circular polarisation incident light. The PG can be driven by 2.5 V/µm electric field with alternating frequency and has no Freedericksz transition threshold. In response time, the rise time and decay time are 650 and 950 , respectively; the sub-millisecond can be achieved under a low driving voltage. Graphical Abstract: